Kontroversi Poligami Bagi Pegawai Negeri Sipil - Amiruddin; Zainal Arifin; Muhammad Ridhona Z. Nur; Siti Jamilah Wisudarsri (Program Studi Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze the regulations and implications of polygamy for Civil Servants (PNS) in Indonesia. The methodology employed is library research with a qualitative and descriptive approach, collecting data from primary and secondary sources to identify patterns and significant information. The findings indicate that although polygamy is permitted under Law No. 1 of 1974, its implementation for PNS is strictly regulated through Government Regulation No. 45 of 1990, which protects the rights of wives and prevents abuse. The conclusion of this research emphasizes that while the Quran permits polygamy, Indonesian positive law places greater emphasis on the principle of monogamy, with the authority to grant polygamy permits resting entirely with the judges of the Religious Court.